The Shh receptor Boc promotes progression of early medulloblastoma to advanced tumors - Mille, Frédéric; Tamayo-Orrego, Lukas; Lévesque, Martin; Remke, Marc; Korshunov, Andrey; Cardin, Julie; Bouchard, Nicolas; Izzi, Luisa; Kool, Marcel; Northcott, Paul A.; Taylor, Michael D.; Pfister, Stefan; et al. (Developmental cell, 2014)
During cerebellar development, Sonic hedgehog (Shh) signaling drives the proliferation of granule cell precursors (GCPs). Aberrant activation of Shh signaling causes overproliferation of GCPs, leading to medulloblastoma. Although the Shh-binding protein Boc associates with the Shh receptor Ptch1 to mediate Shh signaling, whether Boc plays a role in medulloblastoma is unknown. Here, we show that BOC is upregulated in medulloblastomas and induces GCP proliferation. Conversely, Boc inactivation reduces proliferation and progression of early medulloblastomas to advanced tumors. Mechanistically, we find that Boc, through elevated Shh signaling, promotes high levels of DNA damage, an effect mediated by CyclinD1. High DNA damage in the presence of Boc increases the incidence of Ptch1 loss of heterozygosity, an important event in the progression from early to advanced medulloblastoma. Together, our results indicate that DNA damage promoted by Boc leads to the demise of its own coreceptor, Ptch1, and consequently medulloblastoma progression.